Effectiveness of emotional skills training for patients with anorexia nervosa with autistic symptoms in group and individual format. (2nd April 2018) - Adamson, James; Leppanen, Jenni; Murin, Marianna; Tchanturia, Kate
Abstract: Objective: The aim of this study was to examine the effectiveness of CREST interventions in individual and group formats for adult anorexia nervosa. Furthermore, this study also aims to analyse whether patients with high levels of autistic symptoms respond differently. Methods: Participants' self‐report measures were taken before and after individual and group interventions ( N  = 66 and N  = 62, respectively). Mixed effects analysis was used to analyse overall response to both formats and assess interaction with autism symptoms. Results: Significant improvements were observed for patients' alexithymia in individual format, and motivation increased for participants in both interventions. Significant interactions were observed between alexithymia, social anhedonia, and autism symptoms in individual format and alexithymia in group format. No interactions between autism and time were observed for either format. Conclusions: CREST in both formats offers participants improvements in social–emotional and motivational domains. Patients with high levels of autism symptoms also score high on both social anhedonia and alexithymia measures, but this does not affect their response to treatment.